Mapeamento e correlação de atributos do solo e de plantas de café conilon para fins de agricultura de precisão. - Oliveira, Rone Batista de (2007)
The present work insert inside of two extremely important research lines, the agriculture of precision and the culture of the conilon coffee in Espírito Santo state.For the conilon coffee several production technologies exist. However, a little or anythin